2009
DOI: 10.1021/jf9007168
|View full text |Cite
|
Sign up to set email alerts
|

Astragalosides Isolated from the Root of Astragalus Radix Inhibit the Formation of Advanced Glycation End Products

Abstract: Because advanced glycation end product (AGE) inhibitors such as pyridoxamine significantly inhibit the development of retinopathy and neuropathy in the streptozotocin-induced diabetic rat, treatment with AGE inhibitors is believed to be a potential strategy for the prevention of lifestyle-related diseases such as diabetic complications. A crude extract of Astragali Radix (AR; roots of Astragalus membranaceus ) inhibits the formation of N(epsilon)-(carboxymethyl)lysine (CML) and pentosidine during the incubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 30 publications
(38 reference statements)
3
25
0
1
Order By: Relevance
“…We previously reported that Astragalus radix samples for the natural herb-derived compound inhibits formation of CML and pentosidine from the reaction of bovine serum albumin and ribose. Our findings confirmed that astragaloside significantly inhibits both of these AGEs, (22) although the inhibitory effect of the compound has not yet been confirmed in vivo . Furthermore, we also reported that high concentration (>1 mM) of catechol compounds such as epicatechin, gallic acid and 4-MC exhibits enhancing effects of CML formation by producing hydrogen peroxide, 0.01 mM of these compounds inhibits CML formation due to their high antioxidative activity.…”
Section: Inhibitors For Ages Formationsupporting
confidence: 68%
“…We previously reported that Astragalus radix samples for the natural herb-derived compound inhibits formation of CML and pentosidine from the reaction of bovine serum albumin and ribose. Our findings confirmed that astragaloside significantly inhibits both of these AGEs, (22) although the inhibitory effect of the compound has not yet been confirmed in vivo . Furthermore, we also reported that high concentration (>1 mM) of catechol compounds such as epicatechin, gallic acid and 4-MC exhibits enhancing effects of CML formation by producing hydrogen peroxide, 0.01 mM of these compounds inhibits CML formation due to their high antioxidative activity.…”
Section: Inhibitors For Ages Formationsupporting
confidence: 68%
“…Ginsenosides, which belong to PN, can improve lipid profiles, inhibit peroxidation and increase the activity of antioxidant enzymes (Xia, Sun, Zhao, & Hypolipidemic, ). Astragalosides, which are the major constituents of AM, show protective effects on kidney of diabetic rats (Motomura et al, ). The extract of MC displays insulin secretagog and insulinomimetic activity, which may be ascribed to steroidal compounds and polypeptides (Raman and Lau, ).…”
Section: Introductionmentioning
confidence: 99%
“…The root bark of Aralia taibaiensis is a rich source of bioactive components (such as terpenoids and saponins), which have potent antioxidant activities and anti‐inflammatory properties . Previous studies demonstrated that Aralia root bark extract (ARBE) could protect pancreatic β‐cells against oxidative damage and inhibit the glycation reaction, suggesting that ARBE may potentially play a role in the treatment of diabetes . It has not been determined that the combination treatment with ARBE added to glipizide would provide additional effects on blood glucose and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%